Morbidity patterns among the underweight, overweight, and obese between 2 and 18 years: population-based cross-sectional analyses - Carlin, JB; Canterford, L; Waters, E; Patton, G; Wake, M; Williams, J; Clifford, S (My University, 2012)
Context: No study has documented how symptomatic morbidity varies across the body mass index (BMI) spectrum (underweight, normal weight, overweight and obese) or across the entire child and adolescent age range. Objective: To (1) quantify physical and psychosocial morbidities experienced by 2-18-year-olds according to BMI status and (2) explore morbidity patterns by age. Design, setting and participants: Cross-sectional data from two Australian population studies (the Longitudinal Study of Australian Children and the Health of Young Victorians Study) were collected during 2000-2006. Participants were grouped into five age bands: 2-3 (n=4606), 4-5 (n=4983), 6-7 (n=4464), 8-12 (n=1541) and 13-18 (n=928) years. Main measures: Outcomes-Parent- and self-reported global health; physical, psychosocial and mental health; special health-care needs; wheeze; asthma and sleep problems. Exposure-measured BMI (kg m(-2)) categorised using standard international cutpoints. Analyses: The variation in comorbidities across BMI categories within and between age bands was examined using linear and logistic regression models. Results: Comorbidities varied with BMI category for all except sleep problems, generally showing the highest levels for the obese category. However, patterns differed markedly between age groups. In particular, poorer global health and special health-care needs were associated with underweight in young children, but obesity in older children. Prevalence of poorer physical health varied little by BMI in 2-5-year-olds, but from 6 to 7 years was increasingly associated with obesity. Normal-weight children tended to experience the best psychosocial and mental health, with little evidence that the U-shaped associations of these variables with BMI status varied by age. Wheeze and asthma increased slightly with BMI at all ages. Conclusions: Deviation from normal weight is associated with health differences in children and adolescents that vary by morbidity and age. As well as lowering risks for later disease, promoting normal body weight appears central to improving the health and well-being of the young.
International Journal of Obesity
Keywords: Child Development -- Physical; Health -- Obesity; Adolescents and youth; Childhood and child development; Health and wellbeing; Health; Child Development; Obesity; Physical; Childhood and child development; Health and wellbeing